3D printed solid-phase extraction sorbents for removal of volatile organic compounds from water. (June 2020) - Lagalante, Luke A.; Lagalante, Ayden J.; Lagalante, Anthony F.
Abstract: A carbon black modified polylactic acid (PLA) sorbent was 3D printed from a commercially available conductive PLA filament on a personal 3D printer. The internal porosity of the sorbent was controlled through software-controlled infill print densities from 15 to 50%. The 3D printed sorbent was evaluated for its ability to remove model VOC contaminants (benzene, toluene, and ethyl benzene) from water where the pseudo-second order rate constants for VOC sorption were found to increase with a decrease of internal pore size of the sorbent infill density. The ability to 3D print carbon-based sorbents for on-demand, point-of-use water purification presents a potentially useful mechanism for in-home or emergency purification situations where consumption of clean water is not possible.